Prickly pear, potential adsorbent of copper (Cu2+), iron (Fe3+) and chromium (Cr3+) from contaminated waters [Tuna, potencial adsorbente de cobre (Cu2+), hierro (Fe3+) y cromo (Cr3+) de aguas contaminadas] - Morales-Aredo, Jhossep (2020)
ABSTRACT The aim of the study was to evaluate the potential of prickly pear cactus cladode (Opuntia ficus) to remove copper (Cu2+), iron (Fe3+) and chromium (Cr3+) from aqueous solutions. Distilled water mixed with Cu2+, Fe3+ or Cr3+ at initial concentrations of 19.60, 16.60 and 17.85 ppm, respectively, were used as media for testing. The aqueous media were treated with two adsorbents: i) a naturally collected cladode (CT), and ii) a cladode chemically modified with calcium (CTCa). The results indicate that a greater metal adsorption is obtained with the CTCa adsorbent. Moreover, 2 hours of contact is enough to remove up to 82.75, 78.36 and 87.84% of Cu2+, Fe3+ and Cr3+, respectively, with respect to their initial concentrations. Our results suggest that the prickly pear cactus cladode might be potentially effective as an eco-friendly adsorbent for removing heavy metals from contaminated waters.